2017
DOI: 10.3390/ma10101145
|View full text |Cite
|
Sign up to set email alerts
|

Performance Analysis of Retrofitted Tribo-Corrosion Test Rig for Monitoring In Situ Oil Conditions

Abstract: Oils and lubricants, once extracted after use from a mechanical system, can hardly be reused, and should be refurbished or replaced in most applications. New methods of in situ oil and lubricant efficiency monitoring systems have been introduced for a wide variety of mechanical systems, such as automobiles, aerospace aircrafts, ships, offshore wind turbines, and deep sea oil drilling rigs. These methods utilize electronic sensors to monitor the “byproduct effects” in a mechanical system that are not indicative… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 10 publications
(4 citation statements)
references
References 41 publications
(42 reference statements)
0
4
0
Order By: Relevance
“…It has been found in the literature [ 4 , 5 ] that the combined effects of both the mechanical and electrochemical parameters directly influence the electrochemical reactions on the surface of nanocoating. Khan-Nazir [ 6 , 7 ] suggested that electrochemical reactions on metal coating surfaces are stress-dependent.…”
Section: Introductionmentioning
confidence: 99%
“…It has been found in the literature [ 4 , 5 ] that the combined effects of both the mechanical and electrochemical parameters directly influence the electrochemical reactions on the surface of nanocoating. Khan-Nazir [ 6 , 7 ] suggested that electrochemical reactions on metal coating surfaces are stress-dependent.…”
Section: Introductionmentioning
confidence: 99%
“…(1) First, the experiment will be performed using the tribocorrosion monitoring test setup (Figure 1) developed in-house [21]. The setup consists of a pin-on-disk setup, and an electrochemical cell with three-electrode configuration.…”
Section: Tribocorrosion Testsmentioning
confidence: 99%
“…The generation of large micron-sized wear particles (Figure 7a) during sliding causes entrapment of the particles at the asperity interface, which either led to pitting or embedding of the particle on the surface during repeated sliding. Since, steel exhibited moderately high surface energy with similar contact angles for distilled water and 3.5% NaCl, hence it could be expected to be susceptible to corrosion and tribocorrosion [42,61].…”
Section: Friction and Wearmentioning
confidence: 99%